Fostering sustainable growth: Analyzing the impact of financial access and managerial expertise on the growth of small and medium enterprises - Putra P, Komang Widhya Sedana; Lasmi, Ni Wayan; Laksmi P, Kadek Wulandari (Nur Science Institute, 2024)
This study will seek to investigate the effect of access to finance and managerial capability on driving SME growth in Bali, Indonesia. The study used a quantitative research design with a population of 100 legally registered SMEs in Bali, with data collected through questionnaires. The analytical method applied for testing the relationships among variables is PLS-SEM. These results indicate that access to finance is positive for the growth of SMEs, which would lead to business expansion. The interaction between managerial capability and access to finance is also significant in determining growth, underlining that higher managerial competence enhances SMEs' ability to leverage financing for better growth. These findings underline that access to finance needs to be complemented with improved managerial capabilities if sustainable SME sector development is to be supported. These findings imply that policymakers and development programs, apart from the facilitation of access to finance, should be targeting training and capacity-building for entrepreneurship management skills.